Executive programs for Brazilian mid-career public managers: Pitfalls and challenges. Issue 1 (March 2017) - Pacheco, Regina Silvia; Franzese, Cibele
This paper discusses the challenges of professional education for mid-career public managers at graduate level, pointing out pitfalls to avoid and obstacles to face. Analyzing the Brazilian case, the goal is to raise issues that may also be present in other cases. The main argument developed here is that the puzzle faced by graduate programs on public administration requires an equal distance from training and from academic programs. Education programs for professionals in public administration should address their own challenges – namely problem-solving and interdisciplinarity.